Penggunaan Permainan Edukasi pada Pembelajaran Daring Mata Pelajaran Geografi Kelas XII di MA PPPI Miftahussalam Banyumas - Faris Salman Faza (UM Purwokerto Press, 2021)
The existence of the COVID-19 outbreak has an impact on all sectors of life, one of which is in the education sector, many schools are forced to dismiss their students and teaching and learning activities are carried out online. the transition of Geography teaching and learning activities at MA PPPI Miftahussalam Banyumas from face to face to online creates new problems in learning so that a special strategy is needed in this learning. Although online learning is not effective for achieving learning goals, the teacher must be able to make new innovations so that learning objectives can be achieved. This study uses a qualitative description method by observing the behavior of students when online learning takes place. Learning online Geography class XII at MA PPPI Miftahussalam Banyumas uses educational games. This study aims to find out the right media in learning Geography class XII during the COVID-19 pandemic at MA PPPI Miftahussalam Banyumas. The results of this study showed that 76 students of class XII MA PPPI Miftahussalam Banyumas who had taken the test showed an average value> 8.00. This shows satisfactory results.